A new species of bird's nest fungi: characterisation of Cyathus subglobisporus sp. nov. based on morphological and molecular data - R.-L. Zhao; D.E. Desjardin; K. Soytong; K.D. Hyde (My University, 2008)
Recent collections of bird's nest fungi (i.e. Crucibulum, Cyathus, Mycocalia, Nidula, and Nidularia species) in northern Thailand resulted in the discovery of a new species of Cyathus, herein described as C. subglobisporus. This species is distinct by a combination of ivory-coloured fruiting bodies covered with shaggy hairs, plications on the inner surface of the peridium and subglobose basidiospores. Phylogenetic analyses based on ITS and LSU ribosomal DNA sequences using neighbour-joining, maximum likelihood and weighted maximum parsimony support Cyathus subglobisporus as a distinct species and sister to a clade containing C. annulatus, C. renweii and C. stercoreus in the Striatum group.
Keywords: Maximum parsimony; Plant Pathogens and Fungal Diseases